Dengue Fever: Therapeutic Potential of Carica papaya L. Leaves - Sarker, Md. Moklesur Rahman; Khan, Farzana; Mohamed, Isa Naina (Frontiers in Pharmacology, 2021)
Dengue, a very widespread mosquito-borne infectious disease caused by Aedes aegypti virus, has been occurring during the monsoons every year. The prevalence and incidence of dengue fever and death due to its complications have been increased drastically in these recent years in Bangladesh, Philippines, Thailand, Brazil, and India. Recently, dengue had spread in an epidemic form in Bangladesh, Thailand, and Philippines. Although the infection affected a large number of people around the world, there is no established specific and effective treatment by synthetic medicines. In this subcontinent, Malaysia could effectively control its incidences and death of patients using alternative medication treatment mainly prepared from Carica papaya L. leaves along with proper care and hospitalization. Papaya leaves, their juice or extract, as well as their different forms of preparation have long been used traditionally for treating dengue fever and its complications to save patients’ lives. Although it is recommended by traditional healers, and the general public use Papaya leaves juice or their other preparations in dengue fever, this treatment option is strictly denied by the physicians offering treatment in hospitals in Bangladesh as they do not believe in the effectiveness of papaya leaves, thus suggesting to patients that they should not use them. In Bangladesh, 1,01,354 dengue patients have been hospitalized, with 179 deaths in the year 2019 according to information from the Institute of Epidemiology, Disease Control, and Research as well as the Directorate General of Health Services of Bangladesh. Most of the patients died because of the falling down of platelets to dangerous levels and hemorrhage or serious bleeding. Therefore, this paper aims to critically review the scientific basis and effectiveness of Carica papaya L. leaves in treating dengue fever based on preclinical and clinical reports. Thrombocytopenia is one of the major conditions that is typical in cases of dengue infection. Besides, the infection and impairment of immunity are concerned with dengue patients. This review summarizes all the scientific reports on Carica papaya L. for its ability on three aspects of dengue: antiviral activities, prevention of thrombocytopenia and improvement of immunity during dengue fever.